2011
DOI: 10.1007/s10461-011-0053-5
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the HIV/AIDS Epidemic in Transgender Women of Lima, Peru: Results from a Sero-Epidemiologic Study Using Respondent Driven Sampling

Abstract: In Latin America, transgender women (transwomen or male to female transgenders) have been included in MSM research but without addressing their specific needs in terms of the HIV/AIDS. We present results of the first seroepidemiologic study designed for transwomen in Peru. We conducted a study using respondent driven sampling to recruit transwomen from Lima. Our survey explored sociodemographic characteristics, gender enhancement procedures and sexual behavior. In addition, we conducted laboratory based HIV, g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
188
2
10

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 198 publications
(222 citation statements)
references
References 47 publications
(67 reference statements)
14
188
2
10
Order By: Relevance
“…4,7,14,15 We also found that number of partners in the last month was associated with a higher risk of having HIV, similar to other studies. 7,14 No significant associations were found with sexual work, living in a house or ever had lived in the street but our low sample size could explain lack of significance in some of these variables.…”
Section: Discussionsupporting
confidence: 89%
“…4,7,14,15 We also found that number of partners in the last month was associated with a higher risk of having HIV, similar to other studies. 7,14 No significant associations were found with sexual work, living in a house or ever had lived in the street but our low sample size could explain lack of significance in some of these variables.…”
Section: Discussionsupporting
confidence: 89%
“…13 These include gender abuse, such as verbal assaults or physical abuse, 11,22 intimate partner violence, 45 and physical or sexual assaults (38%-50%) that might be frequently targeted toward transgender women. 10,11,22 Other factors include a high prevalence sex work as a main economic activity (64%-67%) in samples of transgender women, 45,46 and a high prevalence of sexual risk behaviors among this population. Past studies also found that transgender women are more likely to report unstable housing and low income than transgender men.…”
Section: Stigma and Mental Health Among Transgender Womenmentioning
confidence: 99%
“…Research focusing on HIV risk among transgender people worldwide has shown that these populations often have high HIV prevalence rates, and increased risk of HIV transmission (De Santis 2009;Nuttbrock, Hwahng, Bockting, Rosenblum, Mason, Macri, et al 2009;Silva-Santisteban, Raymond, Salazar, Villayzan, Leon, McFarland, et al 2011). This research has mainly focused on transgender women, but Stephens, Bernstein and Philip (2010), in a study in San Francisco, USA, found no difference in rates of sexually transmitted infections and HIV between transgender men and transgender women.…”
Section: Introductionmentioning
confidence: 99%